Predominance of regorafenib over sorafenib: Restoration of membrane‐bound MICA in hepatocellular carcinoma cells. Issue 5 (6th February 2018) - Arai, Jun; Goto, Kaku; Stephanou, Anthony; Tanoue, Yasushi; Ito, Sayaka; Muroyama, Ryosuke; Matsubara, Yasuo; Nakagawa, Ryo; Morimoto, Sayuri; Kaise, Yoshimi; Lim, Lay Ahyoung; Yoshida, Hitoshi; et al.
Abstract: Background and Aim: The multi‐kinase inhibitor regorafenib (REG) was recently demonstrated to be effective in patients with sorafenib (SOR)‐resistant hepatocellular carcinoma (HCC). Interestingly, SOR is known to enhance the accumulation of membrane‐bound MHC class I polypeptide‐related sequence A (mMICA) in HCC cells and to block the production of soluble MICA (sMICA), an immunological decoy. In addition, MICA is associated with HCC in patients with chronic hepatitis C. We have now compared the impact of REG and SOR on MICA in HCC cells, as well as the immunotherapeutic implications thereof. Methods: HepG2 and PLC/PRF/5 cells were exposed to REG and SOR, and levels of sMICA and mMICA were measured by ELISA and flow cytometry, respectively. The drugs were also tested in vitro for inhibitory activity against recombinant human A disintegrin and metalloprotease 9 (ADAM9), a sheddase that releases MICA from the membrane. Results: To a greater extent than SOR, but without marked difference in cytotoxicity, REG significantly suppressed mRNA and protein expression of ADAM9 and ADAM10, thereby decreasing production of sMICA and boosting accumulation of mMICA. Accumulation of mMICA in response to REG was reversed by siRNA against ADAM9. However, the drugs did not inhibit the enzymatic activity of ADAM9 in vitro . Conclusions: The clinical superiority of REG over SOR is partially attributable to reduced MICA shedding via transcriptional suppression of ADAM9 and ADAM10.